2013
DOI: 10.1155/2013/247145
|View full text |Cite
|
Sign up to set email alerts
|

A Review on the Anti-Inflammatory Activity of Pomegranate in the Gastrointestinal Tract

Abstract: Several biological activities of pomegranate have been widely described in the literature, but the anti-inflammatory effect in the gastrointestinal tract has not been reviewed till now. The aim of the present paper is to summarize the evidence for or against the efficacy of pomegranate for coping with inflammatory conditions of the gastro-intestinal tract. The paper has been organized in three parts: (1) the first one is devoted to the modifications of pomegranate active compounds in the gastro-intestinal trac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
70
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(73 citation statements)
references
References 65 publications
3
70
0
Order By: Relevance
“…Four hours later, the stomachs were removed and inflated with 10 ml of formalin solution and immersed in the same solution to fix the outer layer of stomach. Each stomach was then opened along the greater curvature, rinsed with tap water to remove gastric content and blood clots and examined under the dissecting microscope to assess the formation of ulcers [8]. The ulcer index [3] and inhibition percentage was calculated according to previous reported [8].…”
Section: Preparation Of Test Samples For Bioassaymentioning
confidence: 99%
“…Four hours later, the stomachs were removed and inflated with 10 ml of formalin solution and immersed in the same solution to fix the outer layer of stomach. Each stomach was then opened along the greater curvature, rinsed with tap water to remove gastric content and blood clots and examined under the dissecting microscope to assess the formation of ulcers [8]. The ulcer index [3] and inhibition percentage was calculated according to previous reported [8].…”
Section: Preparation Of Test Samples For Bioassaymentioning
confidence: 99%
“…Epidemiological studies show that consumption of pomegranate correlates with reduced cardiovascular and cerebrovascular diseases, anti-diabetic and anti-inflammatory activity and reduced cancer mortality [8][9][10][11][12][13][14][15][16][17][18][19]. Other studies suggest that some compounds of the pomegranate juice are characterized by antioxidant, antimicrobial and antiviral activities [20][21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have reported significant anti-inflammatory activity of P. granatum and some conclusions could be drawn from all the studies Firstly, the pure compounds occurring in P. granatum extract appear to act through different pathways. methanol and aqueous extracts from P. granatum peel could inhibit the expression and secretion of several inflammatory mediators such as IL-6, IL-8, MCP-1, iNOS, COX-2, and PGE 2 [28]. Additionally to these conclusions, there are some other studies that indicate P. granatum peel extracts might affect immune responses, for example a study of P. granatum contents exhibited inhibition of inducible nitric oxide synthase (iNOS) expression and NO production in in RAW 264.7 cells [29].…”
Section: Discussion:-mentioning
confidence: 99%